The Influence of The Implementation of Good Corporate Governance and AKHLAK on The Performance - Muhammad Farhan; Habbe, Abdul Hamid; Purisamya, Asharin Juwita (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2024)
This study aims to determine the effect of the implementation of good corporate governance and AKHLAK on the company's performance at PT. Telkom Regional. The method of data collection in this study is to use a questionnaire distributed to employees as primary data. The data were analyzed by multiple linear regression and tested by research instrument test, classical assumption test, partial test and simultaneous test using SPSS software. The results of this study indicate that good corporate governance and AKHLAK has a positive and significant effect on company performance at the PT. Telkom Regional.